Validasi Pengembangan Modul Ajar Bioteknologi Berbasis Problem Based Learning - Zharifa Afifi; Syamsurizal Syamsurizal; Helendra Helendra; Ria Anggriyani (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The Independent Curriculum requires teachers to compile teaching tools consisting of Learning Outcomes (CP), Learning Objectives Flow (ATP) and teaching modules as a mandatory task of a teacher. The teaching module is a form of learning implementation plan in the Independent Curriculum which is accompanied by student worksheets and teaching materials in it. This research uses a type of development research with a 4D model. The 4D model consists of four stages of Define, Design, Develop and Disseminate. Due to time constraints, this study did not carry out the disseminate stage. The subjects of this study consisted of lecturers from the Biology Department, FMIPA UNP, seven Biology teachers. Based on the research data, a problem-based learning biotechnology teaching module is obtained which is very valid with a validation value of 95.59%.